(untitled) (Experimental biology, 2016)
It has been studied protein compounds of the common beans from Kazakhstan, Russian and foreign selection. It has been shown that the protein content in studied cvs varies from 23.2% to 30.8%. The highest protein content is contained in foreign cv. “Iranskaya”(30.8%) and “Zhuravushka” (30.7%) from Russian collection. Cvs “Aktatti” and “Bomba” occupy an intermediate position. The albumin-globulin fraction in the seeds of all studied cvs dominated among other fractions and was 76.2-82.3%. Bioscreening demonstrated that lectine activity of studied cvs depends on the origin of erythrocytes, genotype and ranges from 10 to 13 points. All of cvs have the high titer of lectine (38.3-55.8[mg/ml]-1). The most perspective lines and species for obtaining lectines are cvs “Yubileinaya”, “Zhuravuska” and local cv. “Aktatti”.